2015
DOI: 10.1016/j.scitotenv.2015.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Determining in situ periphyton community responses to nutrient and atrazine gradients via pigment analysis

Abstract: Agrochemicals, including fertilizers and herbicides, are significant contributors of non-point source pollution to surface waters and have the potential to negatively affect periphyton. We characterized periphyton communities using pigment markers to assess the effects of nutrient enrichment and the herbicide atrazine with in situ experimental manipulations and by examining changes in community structure along existing agrochemical gradients. In 2008, the addition of nutrients (20 mg/L nitrate and 1.25 mg/L re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Means with asterisks are significantly (p \ 0.05) different from the control per time reduced the growth and cell density of S. quadricauda, regardless of the N condition. Nitrogen and ATR have contrasting effects on S. quadricauda, with replete nitrogen stimulating growth and ATR inhibiting it (Dalton et al 2015). While there is evidence that low concentrations of ATR can stimulate algal growth (Murdock and Wetzel 2012), all concentrations used in the present study inhibited the growth of S. quadricauda, which is in accordance with the results obtained with several algal species (Guasch et al 2007;Jeannette et al 2007;Vallotton et al 2008;Richard et al 2012;Bai et al 2015;Chia et al 2015a).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Means with asterisks are significantly (p \ 0.05) different from the control per time reduced the growth and cell density of S. quadricauda, regardless of the N condition. Nitrogen and ATR have contrasting effects on S. quadricauda, with replete nitrogen stimulating growth and ATR inhibiting it (Dalton et al 2015). While there is evidence that low concentrations of ATR can stimulate algal growth (Murdock and Wetzel 2012), all concentrations used in the present study inhibited the growth of S. quadricauda, which is in accordance with the results obtained with several algal species (Guasch et al 2007;Jeannette et al 2007;Vallotton et al 2008;Richard et al 2012;Bai et al 2015;Chia et al 2015a).…”
Section: Discussionsupporting
confidence: 89%
“…Selection of these concentrations was based on 96 h EC 50 of atrazine that was obtained in preliminary experiments. This concentration range of atrazine is within environmentally realistic levels (Dalton et al 2015). The final concentration of acetone in the treatments and each control was\0.1 % (v/v) (Tang et al 1997;Qian et al 2008), and preliminary analysis indicated that this concentration had no effect on the growth of the microalga.…”
Section: Atrazine (Atr) and Nitrogen (N) Experimentsmentioning
confidence: 78%
See 3 more Smart Citations